The man from nowhere - Smith, Bernard 1937- (Cambridge English readers. Level 2, 2000)
A man is walking slowly in the desert. He is not wearing a shirt. The sun is on his back, which is burnt red. He cannot see, he cannot think. He does not know where he is or who he is. He only knows that he must keep moving, keep putting one foot in front of the other. Keep moving, or die.